Radial arterial thrombosis in COVID-19: A case report - ÇİÇEK, FURKAN CUMA; EYÜPLER, ÇAĞLA; YETGİNOĞLU, ÖZGE; AK, KORAY; KOCAKAYA, DERYA (My University, 2022)
Thrombosis due to hypercoagulable state is an important cause of morbidity and mortality in coronavirus disease 2019 (COVID-19). Increased D-dimer levels are an important marker of the presence and risk of thrombosis. In this report, we present that a 59-year-old male patient developed thrombosis in the distal radial arteries despite normal D-dimer level. The patient was treated with enoxaparin, iloprost infusion, and cilostazol. This case should lead us to be very careful that people diagnosed with COVID-19 with normal D-dimer levels may also have thrombosis.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; COVID-19; Radial artery; Thrombosis; COMPLICATIONS; COVID-19; Radial artery; Thrombosis